KELIMPAHAN PLANKTON PADA EKOSISTEM PERAIRAN PULAU TEBING TINGGI KABUPATEN KEPULAUAN MERANTI, RIAU - Eddiwan Kamaruddin (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
Research on the abundance of plankton in Tebing Tinggi Island waters ecosystem, Meranti Island District, Riau Province was conducted in March 2017. The observations focused on the phytoplankton and zooplankton communities at ten stations. The variations in the abundance of plankton on average between the location groups were 4428 - 1716224 cells / m3 and 23938 individuals / m3 (67.73%) respectively for phytoplankton and zooplankton. The structure of the phytoplankton community was observed to be dominated by 5 diatoms. Coscinodiscus, Chaetoceros, Guinardia, Navicula, Pseudonitzshia. However, the predominant genus (> 10%) was Coscinodiscus with an abundance of 664,665.97 cells / m3 (99.47%) at station 5. Of the dinoflagellate group, only Ceratium clans with the highest abundance in station 7 of 324609 cells / m3 with location to the north of the Black Water Strait but still in normal condition. The macroplankton community structure is dominated by the Copepoda group especially Calanoida, Cyclopoida and Nauplius copepods with high densities of more than 50%. On the other hand, information about the mangrove forest ecosystem, and associated fauna in the ecosystem in the coastal area of TebingTinggi Island is still lacking. It is therefore necessary to conduct research that can be used as a basis to create a concept of management of marine resources in the region.